Just energy transition and business models: Seeking a strategic management tool for energy communities - Caban, Szymon (Social Entrepreneurship Review, 2025)
Background: Energy communities (ECs) are emerging as key actors in the shift toward a low-carbon and inclusive energy system aligned with the principles of just energy transition (JET). However, conventional business model tools often fail to reflect ECs’ social missions, democratic governance, and environmental goals. Research objectives: This study aims to evaluate the suitability of existing business model frameworks for analyzing ECs and to identify the components necessary for models aligned with JET. Research design and methods: I conducted a qualitative literature review, examining sources to compare conventional and alternative business model frameworks based on criteria derived from JET principles. Results: The analysis found that classical frameworks, such as the business model canvas (BMC), are insufficient for ECs, while alternatives like the triple layered business model canvas (TLBMC), social enterprise model canvas (SEMC), and value mapping tool (VMT) better address ECs’ hybrid organizational logic. Conclusions: Business model innovation must integrate social, environmental, and participatory dimensions to support ECs in advancing a JET.